تطوير معايير إدارة الفعاليات تتوافق مع الشريعة الإسلامية لتلبية متطلبات مؤشرات الشريعة الإسلامية الماليزية (Developing a Sustainable ’Muslim Friendly’ Standards of Event Management in Malaysia) - ياسين روضة الفردوس بنت فتاح; نزري نورالجنة زينان; جاني محمد شاه; الخزيري أكمل (Journal of Islam in Asia (E-ISSN 2289-8077), 2018)
الملخّص لقد أدركت المنظمة الدولية لتوحيد المقاييس أهمية توفير المعايير والمبادئ التوجيهية لإدارة الفعاليات، مما أدى في النهاية إلى إيجاد معيار إدارة الفعاليات أصبح معروفا بـ:ISO 2012 :2012 وهي عبارة عن نظم إدارة استدامة الفعاليات : المتطلبات مع توجيهات استخدامها في عام 2012م المستوحاة أصلا من المعيار البريطاني لإدارة الفعاليات " BS8901" عام 2005. لكن الذي يؤخذ على المعايير المشار إليها سابقا هو عدم مطابقتها مع الشريعة الإسلامية فترُكز هذه المقالة على تطوير المعايير المستدامة لإدارة الفعاليات المطابقة بالشريعة في ماليزيا كونها دولة ذات أغلبية مسلمة. من خلال تطبيق أسلوب تحليل النصوص على الآيات القرآنية والأحاديث النبوية المتعلقة بإدارة الحدث، توصلت الدراسة إلى عدة مبادئ توجيهية هامة والقيم لمعايير لإدارة الفعاليات وهي التوحيد، والوسطية، والاعتدال، والإحسان، والتميز، والإتقان، والجودة وتحقيق مقاصد الشريعة. فجميع هذه العناصر تشكل مفهوما شاملا للإسلام بوصفه الدين وطريقة الحياة التي يسعى إلى ترسيخ الاعتدال والتوازن في كل الأمور، آخذا في الاعتبار اختلاف الديانات والمعتقدات، بما في ذلك من مشاعر غير المسلمين. تشتمل عملية تنظيم هذا الحدث على ثلاث مراحل أساسية؛ وهي: التخطيط، والتنظيم، والرقابة فهي تعتبر أهم الجوانب التي يجب إخضاعها للمبادئ التوجيهية الموضوعة. وتقترح الدراسة نظرة عامة عن معايير إدارة الفعاليات المطابقة بالشريعة الإسلامية التي من شأنها أن تساهم في تحقيق الهدف حتى تكون ماليزيا أحد أهم المراكز في العالم التي تسير على هذه الأسس في إدارةالأحداث. الكلمات المفتاحية: إدارة الحدث، حلال، ماليزيا، الإمتثال للشريعة الإسلامية. Abstract The International Organization of Standardization has realized the importance of providing standards and guidelines for event management, which ultimately led to the existence of event management standard; ISO 20121: 2012 Event sustainability management systems - Requirements with guidance for using it in 2012". It was started out earlier by the British Standard for "’BS8901 Event Management Standard" in 2005. The mentioned standards are not fully compliant with the SharÊʿah requirements. The present study focuses on developing a sustainable ‘Muslim friendly’ standard of event management in Malaysia a Muslim-majority country. By employing textual analysis method on the Quranic verses and the Prophetic hadith related to event management, the study finds several important Guiding Principles (GP) and values for SharÊʿah compliance event management standards (SCEMS) such as al-TawḥÊd (Divine Unity), al-Wasatiyyah (the Moderation), al-TawÉzun (the Balance), al-ʿAdl (the Justice), al-IḥsÉn (the Excellence), al-ItqÉn (the Quality) and MaqÉṣid al-SharÊʿah (The SharÊʿah Objectives). All of these elements are built on a comprehensive understanding of the concept of Islam as a DÊn (Religion) and a way of life which promotes moderation and balance in all matters as well as considers the diversity of faith, including the non-Muslim sentiments. The content and the process of organising an event, which involves three basic phases: Al-TakhÏÊÏ (planning), al-TanẓÊm (organizing) and al-RiqÉbah (controlling) of the event are the most important SharÊʿah based critical point that must adhere to the GP. The study proposes a bird’s eye overview of SharÊʿah compliance event management standards which are vital in achieving the aim of Malaysia to be the SharÊʿah Compliance Hub in the world. Keywords: Event Management, Halal, Malaysia, SharʿÊah compliant.